Coordination inside government administrations: Lessons from the EU Commission. Issue 3 (8th August 2020) - Senninger, Roman; Finke, Daniel; Blom‐Hansen, Jens
Abstract: How can interdepartmental coordination in large political‐administrative systems be organized? This question has vexed scholars and practitioners for more than 100 years. Two perspectives—one that features hierarchical direction and one hallmarked by horizontal negotiation—dominate the scholarly debate. However, we know surprisingly little about how interdepartmental coordination is handled in practice. This article presents an empirical study in an entire political‐administrative system, the EU Commission, and examines whether interdepartmental coordination is hierarchical or negotiated. Our study is based on almost 6, 000 cases and original measures of departmental policy expertise derived from quantitative text analysis. Our results indicate that interdepartmental coordination is primarily driven by concerns of administrative turfs and thus lend support to the negotiated coordination perspective.